Identifikasi Risiko Proyek Konstruksi Flyover dan Underpass di Indonesia(Kajian Literatur) - Vederieq Yahya Enderzon (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2020)
Flyover and underpass are an important part of the road network system, especially to reduce congestion. These flyover and underpass construction projects have unique and very complex characteristics, so they face various types of risks that may occur during the project life cycle. Risks that occur can affect the cost, time and quality of construction projects, which in some cases can even have a serious impact on the sustainability of the project itself. Risk may occur due to several risk factors that cause it. Since the construction of flyover and underpass is very important and is a very strategic and usually large-scale project, a study of the types of risk factors that might occur during the construction of flyovers and underpass in Indonesia is needed. This research is dedicated to answering this problem. This study uses the literature review method for data collection. Based on the results of the study it was found that the risk of the conception stage is an obstacle in land acquisition, the planning stage is a change in design, the implementation stage is safety and safety.